Maternal and fetal factors affecting birth length of healthy newborn babies: An observational study - Dwivedi, Deepak; Verma, Amit (Indian Journal of Child Health, 2015)
Background: Length is an important neonatal measurement at birth. Many studies in the past have analyzed the birth weight and factors affecting it but studies that investigated the relationship between maternal factors and birth length are scarce and inconsistent. Purpose: This study was conducted with the aim to estimate the effect of maternal and fetal factors on birth length in singleton pregnancy. Methods: The present cross-sectional observational study was conducted in a tertiary care center in central India during February 2012. Of 450 deliveries, 191 newborns were included on the basis of inclusion criteria. The weight of the baby was takenby electronic weighing scale, and length was taken with infantometer. Babies were divided into two groups based on Fenton’s chart, and Group A had babies with birth length 3rd centile. The effects of factors such as maternal age, weight during last trimester of pregnancy, education, maternal and paternal height, parity, socioeconomic status, occupation, and residence were assessed. Fetal factors such as birth weight, sex, and birth order were assessed. Results: On analysis of data, it was found that maternal weight (p